Lipid keratopathy and septal abscess: Case report - Heo, Sung Jae (Medicine (Baltimore), 2019)
RATIONALE: Epistaxis is a common otorhinolaryngological emergency, but septal abscess has not been reported before as a complication of epistaxis. PATIENT CONCERNS: We report a case of a 51-year-old man complaining of nasal obstruction and facial numbness for 3 weeks. He had a history of epistaxis, and had been treated with electrocauterization of the left nasal septum at a local clinic 1 month earlier. DIAGNOSES: On nasal endoscopy, swelling of the septum was noticed; computed tomography (CT) was performed, and revealed a septal abscess. INTERVENTIONS: The patient was treated with incision and drainage under local anesthesia. A left vertical hemitransfixion incision was made and 4 mL of purulent material was drained. There was no quadrangular septal cartilage. OUTCOMES: On the 5th postoperative day, the patient complained of blurred vision in his right eye. Visual acuity of the left eye was 0.5, but acuity of the right eye was finger count at 50 cm. Examination of the right eye revealed a whitish fan-shaped corneal opacity on the medial side with neovascularization, diagnostic of lipid keratopathy. CONCLUSION: Electrocautery of epistaxis should be performed carefully during hemostasis, and there should be careful follow-up after the procedure to detect the occurrence of septal hematoma or septal abscess. These conditions should be treated as early as possible to avoid further serious complications. Since lipid keratopathy is difficult to treat once it occurs, care should be taken to avoid a septal abscess.